Towards assisting visually impaired individuals: A review on current status and future prospects - Mashiata, Maisha; Ali, Tasmia; Das, Prangon; Tasneem, Zinat; Badal, Md. Faisal Rahman; Sarker, Subrata Kumar; Hasan, Md. Mehedi; Abhi, Sarafat Hussain; Islam, Md. Robiul; Ali, Md. Firoj; Ahamed, Md. Hafiz; Islam, Md. Manirul; et al. (Biosensors and bioelectronics. X, 2022)
Visually impaired people require support with regular tasks including navigating, detecting obstacles, and maintaining safety, especially in both indoor and outdoor environments. As a result of the advancement of assistive technology, their lives have become substantially more convenient. Here, cutting-edge assistive devices and technologies for the visually impaired are reviewed, along with a chronology of their evolution. These methodologies are classified according to their intended applications. The taxonomy is combined with a description of the tests and experiments that can be used to examine the characteristics and assessments of assistive technology. In addition, the algorithms used in assistive devices are examined. This paper looks at solar industry innovations and promotes using renewable energy sources to create assistive devices, as well as, addresses the sudden advent of COVID-19 and the shift in the development of assistive devices. This review can serve as a stepping stone for further research on the topic. •A detailed categorization of assistive devices and technology used for visually impaired people.•A thorough understanding of the features of assistive devices used for visually impaired people.•An investigation into the necessary tests and studies for the development of assistive devices used for visually impaired people.•A discussion of the benefits of assistive devices used for visually impaired people powered by renewable energy sources.•An evaluation of assistive devices for visually impaired people including the pre- and post-pandemic (COVID-19) phases.